PEDAGOGICAL ELEMENTS AND MORAL EDUCATION IN HÜSEYIN RAZI’S WORK “INNOVATIVE MODEL OR A BUNCH OF LETTERS FOR CHILDREN” - Serdar DERMAN (Fırat University, 2019)
Hüseyin Razi is an author who lived in 19th century. Besides his work “Innovative model or a bunch of letters for children”, he also wrote “Peymane (Wineglass)”, “Pervane (Fan)”, “İkizler Kütüphanesi (Twins Library, co-authored with Erganili Mesut Efendi), “Tahsil-i Kıraat (Teaching Reading). On its cover, information about the book such as a statement “It was published by the permission of Ministry of Education”, published in İstanbul and the owner of Asır library and the publisher was Kirkor and it was published in Kaspar Publishing House on Babıali Street no. 25 in 1307 (the year of the hegira) was given. No study was found on these letters in the literature. The aim of the current study was to determine the educational elements in this work, which was written in 19th century, and examine it in terms of moral education. Thus, it was also aimed to reveal the features of these texts used as teaching materials in the 19th century. The results of the current study indicate that, although it was written in the 19th century, this work, with educational elements and values education system, has the potential to meet current educational needs. The use of such letters in the teaching of Turkish language is likely to motivate learners and keep their interests alive.